Enhanced generation of angle correlated photon-pairs in nonlinear metasurfaces. (1st March 2022) - Mazzanti, Andrea; Parry, Matthew; Poddubny, Alexander N; Della Valle, Giuseppe; Neshev, Dragomir N; Sukhorukov, Andrey A
Abstract: We reveal that strongly enhanced generation of photon pairs with narrow frequency spectra and sharp angular correlations can be realised through spontaneous parametric down-conversion in metasurfaces. This is facilitated by creating meta-gratings through nano-structuring of nonlinear films of sub-wavelength thickness to support the extended bound state in the continuum resonances, associated with ultra-high Q -factors, at the biphoton wavelengths across a wide range of emission angles. Such spectral features of photons can be beneficial for various applications, including quantum imaging. Our modelling demonstrates a pronounced enhancement, compared to unpatterned films, of the total photon-pair generation rate normalized to the pump power reaching 1.75 kHz mW −1, which is robust with respect to the angular bandwidth of the pump, supporting the feasibility of future experimental realisations.